(untitled) (Research, Society and Development, 2020)
It is noticeable the increase in the demand for non-renewable raw materials for applications in the most varied segments of civil construction, which in fact causes more significant damage to the environment, whether through the waste generated during extraction, during use, or after use. In this sense, this work aims to present the state-of-the-art corresponding to the concretes currently developed, emphasizing those of a sustainable scope that corroborate the ecological proposal in the use of residues and/or tailings from different sectors of industrial production, in order to partially settle the slag produced by converting them into raw materials for reuse. The increase in proposals to mitigate environmental impacts with a focus on using these wastes becomes evident. The corresponding study area requires greater expansion of the employment possibilities for improving the technique of incorporating waste into concrete with due observance of the dosage, consumption, packing factor when necessary, density of materials involved, and application aspect of the composite.